Adventures in Sustainable Urbanism - Krueger, Robert; Freytag, Tim (State University of New York Press, 2019)
In the context of urban sustainable development, the "details" of sustainability's current expressions perpetuate environmental injustice, untenable growth, and the destruction of functioning ecosystems. In response to this state of affairs, Adventures in Sustainable Urbanism aims to prompt new debates about the consequences of sustainable urbanism as it moves from planning to practice. Contributors explore policy, practice, and experience from cities around the world, including Calgary, Christchurch, Dortmund, Vancouver, and others. Written by scholars who live in these cities, chapters offer empirically rich descriptions for opening up new lines of thinking, theorizing, and debate about the sustainable city and its actual material expressions in place. By examining the sustainable city through various analytical framings, contributors urge readers to move from viewing the sustainable city as something everyone can agree on, to a highly politicized and contested process. Additional resources are provided for readers who may wish to extend their own research into a city or theme.